An Analysis of the Intertextuality of the Book of Job in the Old Testament Bible - Situmorang, Kosmartua (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The story of Job is a story that is familiar to the three major religions in the world, namely Christianity, Islam and Judaism. For Christianity and Judaism, the story of Job is recorded as a long writing so that it is made into a separate book. The book of Job has problems that have caused much debate, such as whether the story of Job actually exists, who the author is and when it was written, what genre the book is. This article seeks an approach that can provide solutions to these problems. The method used in this research is a qualitative research method by conducting a literature search of both primary sources, namely the text of Job which is intertextual with other books in the Bible. Also, secondary sources are comments or ideas from other authors that are relevant to this research. From the results of the research, it turns out that by using the intertextual approach, alternative answers to the problems in the book of Job were found. Therefore, the intertextual approach of the Bible can be an approach in interpreting the Bible.